The Characteristic Of Geographical And Socio-Economic Conditions Of Farmers In Peatland Rasau Jaya Tiga Village - Hayatullah, Addin Nur; Ulfah, Maria; Adlika, Nur Meily; Asriati, Nuraini (GEOREFERENCE, 2024)
This study aims to determine the characteristics of the geographical conditions and socio-economic conditions of farmers in the peatlands of Rasau Jaya Tiga Village. This research uses mixed-method research with a sequential explanatory design approach. Geographical condition data were processed using spatial pattern analysis which was tested for accuracy using area sampling techniques. Data collection on the socio-economic conditions of peatland farmers was followed by qualitative steps and procedures with three classifications of peatland farmers as participants. The results showed that the characteristics of the soil types in the village of Rasau Jaya Tiga were dominated by organosol soils, with rainfall of 2,001 "“ 2,500 mm/year, and the dominating of land cover was gardens/plantations. The accuracy test results on the land use map are 81.25%. The characteristics of the socio-economic conditions of peatland farmers are marked by adequate monthly income, decent living conditions, a good level of health where nutrition and nutrition aret, good access to health services, but poor individual health insurance, a high level of educational awareness, and understand the importance of knowledge. There are very few social relations (farmer groups) only found in rice farmers. Soil and climate conditions in the village of Rasau Jaya Tiga have a significant impact on the level of productivity of farming land. Farmers understand and can adapt to peatlands in the village of Rasau Jaya Tiga.